A hierarchical interdigitated flow field design for scale-up of high-performance redox flow batteries. (15th March 2019) - Zeng, Yikai; Li, Fenghao; Lu, Fei; Zhou, Xuelong; Yuan, Yanping; Cao, Xiaoling; Xiang, Bo
Graphical abstract: Highlights: A hierarchical interdigitated flow field (HIFF) is proposed for flow batteries. HIFF has independently regulated and hierarchical flow channels. HIFF significantly reduces pump loss and enhances battery performance. Abstract: The pumping loss of redox flow batteries increases dramatically when scaling up to large-area cells, and becomes a key limiting factor for engineering high-performance cell stacks. This work proposes a hierarchical interdigitated flow field design that has independently regulated distribution/collection channels to lower pumping loss and enhance mass transport: a small quantity of primary branch channels with larger section area is engineered to transport the electrolyte across the length of the entire electrode with a relatively low pressure drop, while a large number of secondary branch channels with smaller section area serve to inject the electrolyte into the adjacent porous electrode with a relatively high velocity to ensure good mass transport. The analytical and experimental methods are combined to understand the mass transport phenomena in the presented flow field. It is shown that the hierarchical interdigitated flow field can significantly reduce the pumping loss by 65.9% and increase the pump-based voltage efficiency from 73.8% to 79.1% at 240 mA cm −2 and 3.0 mL min −1  cm −2 compared with the conventional interdigitated flow field, which demonstrates that the hierarchical interdigitated flow field presents a promising solution for scaling up the high-performance redox flow batteries.